2019
DOI: 10.1103/physrevb.99.155412
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent quantum Monte Carlo simulation of electron devices with two-dimensional Dirac materials: A genuine terahertz signature for graphene

Abstract: An intrinsic electron injection model for linear band two-dimensional (2D) materials, like graphene, is presented and its coupling to a recently developed quantum time-dependent Monte Carlo simulator for electron devices, based on the use of stochastic Bohmian conditional wave functions, is explained. The simulator is able to capture the full (DC, AC, transient and noise) performance of 2D electron devices. In particular, we demonstrate that the injection of electrons with positive and negative kinetic energie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Finally, in the orange solid (triangle) curve, dissipation due to acoustic and optical phonons is considered. This last curve confirms that the electron transport is mainly ballistic [21], [22].…”
Section: (A) Schematic Of a Dual-gate Gfet The Central (Pink) Region Corresponds To The Device Active Region Of The Gfet And The Surface supporting
confidence: 71%
See 1 more Smart Citation
“…Finally, in the orange solid (triangle) curve, dissipation due to acoustic and optical phonons is considered. This last curve confirms that the electron transport is mainly ballistic [21], [22].…”
Section: (A) Schematic Of a Dual-gate Gfet The Central (Pink) Region Corresponds To The Device Active Region Of The Gfet And The Surface supporting
confidence: 71%
“…The blue (square) dashed curve in Fig. 1(b) corresponds to the scenario where electrons are injected from both CB and VB from the zerogap graphene [21], [22]. Contrary to normal transistors, we see in the blue curve that there is no saturation current since applying more voltage between the source and drain leads to more carriers traveling from the source to drain from the VB in the source contact to the CB in the drain contact [23].…”
Section: A Natural Explanation From a Bohm-like Realitymentioning
confidence: 95%
“…Because of their dependence on such external parameter, these states are called conditional states (or conditional wave functions). As explained recently 23,24 , Gambetta and Wiseman 25,26 showed that the physical connection of a property of one conditional states between different times requires a quantum theory (like Bohmian mechanics) where the definition of a conditional state has a clear physical (not only mathematical) meaning. In this work, we will use the BITLLES simulator [27][28][29][30][31][32][33] , developed following this second strategy, to provide numerical support to the conclusions of THz noise in ultra-small electron devices.…”
Section: Total (Displacement Plus Particle) Current and Noise In Quanmentioning
confidence: 98%
“…Specifically, in the BITLLES simulator the first and second terms in Equation ( 16) are evaluated through the solution of the Poisson equation [57]. The third and fourth terms are modeled by a proper injection model [66] as well as proper boundary conditions [56,61,67] that include the correlations between active region and reservoirs. Electron-phonon decoherence effects can be also effectively included in Equation ( 15) [27].…”
Section: Bohmian Conditional Wavefunction Approach To Quan-tum Electr...mentioning
confidence: 99%